2014
DOI: 10.1002/aenm.201301886
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of a Composition Tolerant Bulk Heterojunction Blend

Abstract: Extensive internal electron donor (D)/ acceptor (A) interfaces promote charge separation, while the D and A domains lead to effi cient charge carrier transport. Also worth noting is that the components' domain size should be commensurate with the exciton diffusion length and delocalization (≈10 nm) [ 4 ] to maximize charge generation. [ 5 ] The detailed morphology of the donor and acceptor domains within the BHJ material is therefore a principal factor for effi cient charge generation in the fi lm and current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
34
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 30 publications
2
34
0
Order By: Relevance
“…
the donor-acceptor ratio, [7][8][9] the molecular weight, [10][11][12][13] side-chain engineering, [14][15][16] choice of solvent, [17][18][19] fl uorine substitution, [ 20 ] solvent mixtures, [ 21 ] additives, [ 22,23 ] solvent, [ 21,[24][25][26][27] and thermal annealing. [ 28 ] Although the power conversion effi ciency (PCE) of organic BHJ solar cells continues to increase, there has been a growing interest in quantifying the mechanisms and morphology that affect device performance.
…”
mentioning
confidence: 99%
“…
the donor-acceptor ratio, [7][8][9] the molecular weight, [10][11][12][13] side-chain engineering, [14][15][16] choice of solvent, [17][18][19] fl uorine substitution, [ 20 ] solvent mixtures, [ 21 ] additives, [ 22,23 ] solvent, [ 21,[24][25][26][27] and thermal annealing. [ 28 ] Although the power conversion effi ciency (PCE) of organic BHJ solar cells continues to increase, there has been a growing interest in quantifying the mechanisms and morphology that affect device performance.
…”
mentioning
confidence: 99%
“…Moreover, the toxicity of 2-MeTHF is lower than that of commonly used halogenated and aromatic solvents, such as chlorobenzene and chloroform (CHCl 3 ). [36] An initial set of tests demonstrated that the solubility of X2 in 2-MeTHF at room temperature is approximately 29 mg mL À1 , which proved to be sufficient for casting films of more than 300 nm thickness. [32][33][34] It seemed reasonable to examine X2 as the molecular donor (see Scheme 1 for molecular structures).…”
mentioning
confidence: 99%
“…[38] Analysis of the results shown in Figure 2 provided hole mobilities of 2.1 10 À4 cm 2 V À1 s À1 (CHCl 3 ) and 5.6 10 À4 cm 2 V À1 s À1 (2-MeTHF). An examination of previous work [36] led us to focus on the fabrication of X2:PC 61 BC 8 with 60:40 and 50:50 ratios. [39] BHJ devices fabricated from either CHCl 3 or 2-MeTHF were characterized in parallel to investigate the photovoltaic properties.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is evident that these imaging conditions produce completely dissimilar contrast. The analytical TEM techniques which have been employed to enhance contrast in OPV systems include elemental mapping by EDX [47,48] or core-loss EELS [48,49], mapping variations in the plasmon peak position [42,44,45,[50][51][52][53][54] as well as single electron excitations in the low-loss region of the EEL spectrum [45]. …”
Section: Bright Field Tem Imagingmentioning
confidence: 99%